2002
DOI: 10.1200/jco.2002.20.5.1278
|View full text |Cite
|
Sign up to set email alerts
|

CD20 Expression in Hodgkin and Reed-Sternberg Cells of Classical Hodgkin’s Disease: Associations With Presenting Features and Clinical Outcome

Abstract: CD20 is expressed by HRS cells in 22% of patients with classical HD but is not associated with different FFS after treatment with equivalent regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
3
27
0
4
Order By: Relevance
“…Overexpressed BAX accelerates apoptotic death induced by cytokine deprivation in an IL-3-dependent cell line. Overexpressed BAX also counters the death-repressor activity of Bcl-2 [16]. The expression of the BAX gene is regulated by the tumor suppressor P53 and has been shown to be involved in P53-induced apoptosis.…”
Section: Introductionmentioning
confidence: 98%
“…Overexpressed BAX accelerates apoptotic death induced by cytokine deprivation in an IL-3-dependent cell line. Overexpressed BAX also counters the death-repressor activity of Bcl-2 [16]. The expression of the BAX gene is regulated by the tumor suppressor P53 and has been shown to be involved in P53-induced apoptosis.…”
Section: Introductionmentioning
confidence: 98%
“…CD20 is a transmembrane protein involved in B cell growth and differentiation. Rassidakis et al reported that CD20 was expressed by HRS cells in 22% of patients with classical Hodgkin disease [4]. Eberle et al reviewed the histopathology of Hodgkin lymphoma and immunostaining available for diagnosis in clinical settings [5].…”
Section: Immunostains For Diagnosis Of Hodgkin Lymphomamentioning
confidence: 98%
“…In fact, several naked and conjugated monoclonal antibodies targeting surface proteins that are expressed on the malignant Hodgkin and Reed-Sternberg (HRS) cells are currently under intensive investigation, with promising early results (Table 1). Of particular interest is the CD20 antigen, because it is expressed not only on a fraction of HRS cells but also on the benign reactive B cells in the microenvironment [4]. CD20 can be targeted by rituximab, a commercially available chimeric antibody that is approved by the US Food and Drug Administration for the treatment of CD20-positive B-cell non-Hodgkin lymphoma.…”
Section: Introductionmentioning
confidence: 99%